The Community Reinvestment Act, Lending Discrimination, and the Role of Community Development Banks - Dimitri B. Papadimitriou; Ronnie J. Phillips; L. Randall Wray (Levy Economics Institute of Bard College, 1993)
The Community Development Banks (CDBs) should not be seen as a substitute for the Community Reinvestment Act (CRA) or for other programs designed to revitalize lower income areas. Rather, they should be seen as a complement for existing programs and for other programs that will be proposed by the Clinton administration. As discussed above, the CRA process ensures that a dialogue takes place among regulators, financial institutions, and served communities: it ensures that banks identify their communities and that they satisfy some of the needs of these communities. Moreover, it helps to expand the awareness of bankers such that their expectations about presently undeserved areas are revised. It is unrealistic to expect that any financial institution can meet all the needs of any community; this, there is a role for a CDB to play in some communities that supplements the role played by traditional financial institutions. Similarly, while we believe that CDBs have an important role to play in revitalizing low income communities, we certainly do not see these as a substitute for the wide range of programs (both public and private) that will be needed to reverse long trends of deterioration experienced by some distressed communities. Finally, the CDBs are not intended to be welfare programs but to provide services to the community's residents, and consequently, they must meet the long-run market tests of profitability. Aside from the service aspect, community development banks will: (i)improve the well-being of our citizens not now served because of unresponsive, yet traditional loan qualification norms, and (ii) directly increase the opportunities for potential entrepreneurs and potential employees. The basic assumption underlying the community development bank is that all areas of the country need banks that are clearly oriented toward the small customer: households that have a small net worth, a small IRA account, and a small transactions account, and businesses that need financing measured in thousands rather then millions or billions of dollars.
Keywords: 330